2022
DOI: 10.1021/acsami.2c09272
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt Molybdenum Nitride-Based Nanosheets for Seawater Splitting

Abstract: The development of cost-effective bifunctional catalysts for water electrolysis is both a crucial necessity and an exciting scientific challenge. Herein, a simple approach based on a metal–organic framework sacrificial template to preparing cobalt molybdenum nitride supported on nitrogen-doped carbon nanosheets is reported. The porous structure of produced composite enables fast reaction kinetics, enhanced stability, and high corrosion resistance in critical seawater conditions. The cobalt molybdenum nitride-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…The MX chalcogenide is produced by the reaction of the zerovalent chalcogen (X 0 ) powder with N 2 H 4 ·H 2 O to form X 2– and the immediate reaction of such anions with the metal cations in the metal salt solution. In this way, Ag 2 S, Ag 2 Se, CuS, Cu 2 S, Cu 2 Se, Bi 2 S 3 , Bi 2 Se 3 , PbS, and PbSe particles, which through proper processing can be used in a plethora of different applications, were easily and rapidly obtained. Figure b–d displays scanning electron microscopy (SEM) images of Ag 2 Se produced from different AgNO 3 :Se molar ratios; 2:1, 1.9:1, and 1.8:1.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The MX chalcogenide is produced by the reaction of the zerovalent chalcogen (X 0 ) powder with N 2 H 4 ·H 2 O to form X 2– and the immediate reaction of such anions with the metal cations in the metal salt solution. In this way, Ag 2 S, Ag 2 Se, CuS, Cu 2 S, Cu 2 Se, Bi 2 S 3 , Bi 2 Se 3 , PbS, and PbSe particles, which through proper processing can be used in a plethora of different applications, were easily and rapidly obtained. Figure b–d displays scanning electron microscopy (SEM) images of Ag 2 Se produced from different AgNO 3 :Se molar ratios; 2:1, 1.9:1, and 1.8:1.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Materials with large surface areas are required in numerous technological fields, including catalysis, sensing, environmental remediation, and electrochemical energy storage. Such materials are usually produced using sol–gel routes that involve the reaction, hydrolyzation, and/or condensation of an ionic precursor. The main advantage of such sol–gel procedures is their facile scalability for the production of large amounts of materials.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic approaches developed for SnTe-based materials include the high-temperature melting method, ,, mechanical alloying, melt spinning, self-propagating high-temperature synthesis, , solvothermal method, microwave method, , and aqueous solution method . Among them, the bottom-up engineering of composites using solution-processed nanocrystals as building blocks is a particularly scalable, low-cost, and extremely versatile approach to optimize the performance in numerous applications. Within this approach, the use of inorganic ligands or molecular precursors to adjust the nanocrystal surface composition and to produce nanocomposites with controlled phase distribution has emerged as an especially suitable strategy. In this direction, we have recently reported the preparation of tin chalcogenides such as SnSe 2 , SnSe, and SnS 2 using molecular precursor inks. Besides, we recently demonstrated that a CdSe ligand could act as a secondary phase during the nanocomposite consolidation to modify the electronic band structure of the SnTe matrix, reaching ZT values up to 1.3 at 850 K .…”
Section: Introductionmentioning
confidence: 99%